2010
DOI: 10.1039/b920232n
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative structure-directing effect in the synthesis of aluminophosphate molecular sieves in ionic liquids

Abstract: In situ two-dimensional NMR and fluorescence emission spectroscopy were employed to investigate the cooperative structure-direction effect of organic amine such as morpholine in the synthesis of aluminophosphate molecular sieves in ionic liquids. In situ rotating frame nuclear Overhauser effect spectra (ROESY) together with fluorescence measurements demonstrate that the aggregates between imidazolium cations and morpholines through intermolecular hydrogen bonds can be formed in the gel during the crystallizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…In addition, the interplay of ILs with additives or directing agents has to be investigated further. Therefore, either in situ reaction monitoring [60,61,62] or comparisons of several syntheses can elucidate the influence of ILs. The present review article aims to highlight a variety of reaction parameters and techniques for the directed synthesis of polyions of heavy main-group elements (fourth period and beyond) in ILs (cation and anion abbreviations in Table 1) in order to provide researchers with an insight into promising synthetic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the interplay of ILs with additives or directing agents has to be investigated further. Therefore, either in situ reaction monitoring [60,61,62] or comparisons of several syntheses can elucidate the influence of ILs. The present review article aims to highlight a variety of reaction parameters and techniques for the directed synthesis of polyions of heavy main-group elements (fourth period and beyond) in ILs (cation and anion abbreviations in Table 1) in order to provide researchers with an insight into promising synthetic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Under nonhydrothermal conditions, this question becomes even more pertinent. [9][10][11][12] To date, a number of in situ crystallization studies probing microporous aluminophosphate synthesis exist, the majority of which focus on (Co)APO-5 (AFI structure). These studies utilize mostly scattering methods for probing the onset of crystallization, although many also employ spectroscopic techniques allowing for atomic/molecular insight into the self-assembly process.…”
Section: ' Introductionmentioning
confidence: 99%
“…However, at a high %EU, in which there is an excess of SDAs, high t c values provide solids with high crystallinity and low ion exchange capacity which could be explained by the small microporous structure of the GIS topology and AlPO-CJ2. Also, this probably impedes the balance cation allocation and generates lower charge density in the framework [9,11]. In short, the results showed that crystallization is an extremely complex process involving the interaction and competition between the solvent, template and framework formation.…”
Section: Ion Exchange Capacitymentioning
confidence: 88%
“…These liquids and eutectic mixtures are formed by fused salts (generally formed using organic cations and inorganic anions) at close to ambient temperatures and they can act either as solvents or templates during the synthesis of molecular sieves [2,3]. Although ionothermal synthesis is a potential technique to prepare microporous materials, such as aluminophosphates (AlPOs) [4][5][6][7][8][9][10][11][12][13], the role of the several synthesis parameters in the structure and properties of the zeotype must be well understood.…”
Section: Introductionmentioning
confidence: 99%